Depressão e ansiedade no contexto escolar: reflexão sobre a saúde mental dos estudantes das escolas públicas no município de Bragança-PA - CONCEIÇÃO, Sumara Maria Lima da (2024)
This study addressed the understanding of depression and anxiety in the school context among adolescents, considering adolescence as a critical phase of development associated with intense biopsychosocial changes. Given the severity of these mental health conditions, this research aimed to expand studies on depression in adolescents, associating it with the presence of anxiety, common in depressive disorders. The study highlighted advances in mental health public policies, such as the establishment of Child and Adolescent Psychosocial Care Centers (CAPSi) and emphasized the importance of addressing mental health within the school environment, given the various sources of anxiety in this setting. The methodology involved the analysis of data collected at CAPSi, questionnaires administered to 9th grade students, 1st-year high school students, and 4th stage of Adult Education (EJA) students at the Coronel Aluízio Ferreira Pinheiro State Elementary and High School in Bragança-PA. The Beck Inventory was used to assess the severity of mental health disorder symptoms. The research results revealed a prevalence of mild anxiety symptoms among students, emphasizing the need for public policies to promote mental health in schools. Analysis of the depression questionnaires showed that 48.2% of students exhibited a moderate frequency of depressive symptoms, indicating the need for psychosocial interventions. Additionally, the research detailed the landscape of CAPSi, highlighting its role in treating mental disorders in adolescents. It was observed that the center adopts comprehensive approaches, including individual sessions, therapeutic groups, and artistic practices, aiming to improve and reduce mental health issues. In summary, this work underscored the importance of understanding and addressing the mental health of adolescents in the school environment, proposing strategies for preventing, identifying, and treating depression and anxiety in this age group.